Web-based speech recognition platform SG decoding - Lie, Aileen Laksmono (Nanyang Technological University, 2023)
This project aims to improve a speech-to-text web application that enables users to transcribe audio both offline and in real-time using their microphone. It introduces new features, such as live transcription and collaborative editing, to enable users to transcribe audio in real-time, create notes, and collaborate with colleagues. These features address the growing demand for efficient note-taking tools and remote collaboration, especially in light of the pandemic. The project also uses modern cloud technologies to enhance the web application’s reliability, security, and scalability. The report outlines the steps taken to complete the project, including requirement gathering, UI and system design, implementation, testing, and deployment.